Respuesta :

Answer:

[tex] \boxed{D. \: (f-g)(x) = {x}^{2} + 4x + 3} [/tex]

Given:

[tex]f(x) =2 {x}^{2} - 5 \\ g(x) = {x}^{2} - 4x - 8[/tex]

To find:

[tex](f - g)(x) = f(x) - g(x)[/tex]

Step-by-step explanation:

[tex] \implies(f - g)x = f(x) - g(x) \\ \\ \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: = (2 {x}^{2} - 5) - ( {x}^{2} - 4x - 8) \\ \\ \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: = (2 {x}^{2} - 5) + (- {x}^{2} + 4x + 8) \\ \\ \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: = 2 {x}^{2} - 5 - {x}^{2} + 4x + 8 \\ \\ \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: = 2 {x}^{2} - {x}^{2} + 4x - 5 + 8 \\ \\ \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: = {x}^{2} + 4x + 8 - 5 \\ \\ \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: = {x}^{2} + 4x + 3[/tex]

ACCESS MORE